Literature Review: Development of silicone elastomer composite materials for capping machine silicone rollers - Umarwan, Arie; Tarigan, Kontan (Teknik Mesin - Universitas Muhammadiyah Cileungsi, 2025)
Silicone elastomers are widely used in industrial applications due to their mechanical properties and resistance to temperature and chemicals. In the manufacturing sector, particularly in bottle and jar capping machines, silicone is utilized as the base material for rollers operating under high dynamic loads. These conditions often lead to rapid wear and degradation of the silicone rollers during production processes. This study aims to review various literature sources related to the optimal composition and reinforcement methods for silicone elastomers to determine suitable formulations for roller capping applications. The research was conducted through a literature review of scientific journals published within the last ten years, focusing on the influence of filler type, crosslinker type, and composition on mechanical properties such as tensile strength, tear strength, and elongation at break. The review results indicate that a combination of fumed silica (0.2 phr) and clay (1 phr), along with a peroxide-based crosslinker (3 phr), provides the best mechanical performance, achieving a tensile strength of 6.9 MPa, tear strength of 21.5 kN/m, and elongation at break of 315%. In conclusion, the optimal reinforcement of silicone elastomers depends on the type of filler and crosslinking system used, which directly affects the material’s strength, elasticity, and thermal resistance